The sociolinguistics of banking: language use in enhancing capacities and opportunities - Abdullah, Ain Nadzimah; Talif, Rosli (Universiti Putra Malaysia Press, 2002)
The use of BM (the national language) and English offers economic profitability to private sector employees in Malaysia. Employers see BM-English bilingualism as an important tool for commercial development since it can open doors to new markets and provide for the country's visibility on the international scene (Rosli Talif and Ain Nadzimah 1998). However, a problem facing BM English bilingualism in Malaysia is the lack of agreement as to its purpose and aims. Even after considering the advantages associated with BM-English bilingualism and the contexts in which it is promoted, sustained and developed, many are concerned about its effects on the national language. The debate seems to be about whether promoting English as a tool of development would confine BM to the backwoods. The purpose of this study is to investigate the necessity and use of Bahasa Malaysia (BM) and English among executive-level employees in the banking industry. The industry was selected as it reflects a business that is global, multicultural and multilingual. A survey questionnaire and participant interviews were conducted involving the Central Bank, local and international banks in Kuala Lumpur, Malaysia. Contexts of use for languages used in communication, oral and written, within the banking industry were identified.